2020
DOI: 10.3390/polym12051151
|View full text |Cite
|
Sign up to set email alerts
|

Development of ZnO Nanoflake Type Structures Using Silk Fibres as Template for Water Pollutants Remediation

Abstract: We have fabricated ZnO nanoflake structures using degummed silk fibers as templates, via soaking and calcining the silk fibers bearing ZnO nanoparticles at 150 °C for 6 h. The obtained ZnO nanostructures were characterized using scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), and UV-vis and fluorescence spectroscopic analysis. The size (~500–700 nm) in length and thicknesses (~60 nm) of ZnO nanoflakes were produced. The catalysis performances of ZnO nanoflakes on silk fibers (ZnSk) via ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Due to its antimicrobial activity, this composite scaffold delays pore clogging caused by biological contamination and is suitable for long-term use. Another example, ZnO nanosheets were synthesized by Rao et al [107] through a hydrothermal method using silk fibers as templates. The composite maintained a degradation efficiency of over 97 % for naphthalene even after 12 cycles.…”
Section: Disinfectionmentioning
confidence: 99%
“…Due to its antimicrobial activity, this composite scaffold delays pore clogging caused by biological contamination and is suitable for long-term use. Another example, ZnO nanosheets were synthesized by Rao et al [107] through a hydrothermal method using silk fibers as templates. The composite maintained a degradation efficiency of over 97 % for naphthalene even after 12 cycles.…”
Section: Disinfectionmentioning
confidence: 99%
“…The physical–chemical properties of SBBMs also play an important role in their potential applications. For instance, mineralized SF fibers with ZnO exhibit good photocatalytic properties, making them useful in the field of photodegradation of organic matter . Additionally, due to the excellent electrical conductivity of materials such as CoxP, Fe 7 O 8 , and metal–organic frameworks (MOFs), SBBMs have potential applications in electrical-related fields, such as sensing, bioelectrical resistance, and energy storage …”
Section: Silk Proteins As Templates To Guide the Formation Of Mineral...mentioning
confidence: 99%
“…Sha et al 16 successfully prepared single-crystalline wurtzite ZnO nanorods on carbon bers and experimental results showed an outstanding degradation of MB solution and good recyclability. Most prepared ZnO had mainly one-dimensional and twodimensional morphologies in the current literature, and the multidimensional morphology of ZnO was seldom reported; [17][18][19] moreover, ZnO only reacts in the ultraviolet region due to its nature, so researchers adopted doping modication to expand its application in visible light. [20][21][22] Nithya et al 23 introduced Mn doped nano-sized ZnO, which was prepared by a chemical precipitation method, and the results showed that the band gap of Mn doped ZnO was obviously reduced, and the degradation of BG dye solution reached 97.47% under solar light, which showed outstanding photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%